Human Immune System Mice With Autologous Tumor for Modeling Cancer Immunotherapies - Sun, Liguang; Jin, Chun-Hui; Tan, Shulian; Liu, Wentao; Yang, Yong-Guang (Frontiers in Immunology, 2020)
Mouse models are the most commonly used in vivo system for biomedical research, in which immune-related diseases and therapies can be investigated in syngeneic and immunologically intact hosts. However, because there are significant differences between rodent and human, most findings from conventional mouse models cannot be applied to humans. The humanized mouse with a functional human immune system, also referred to as human immune system (HIS) mouse, is the only model available to date for in vivo studies in real-time of human immune function under physiological and pathological conditions. HIS mice with human tumor xenografts are considered an emerging and promising in vivo model for modeling human cancer immunotherapy. In this review, we briefly discuss the protocols to construct HIS mice and elaborate their pros and cons. Particular attention is given to HIS mouse models with human tumor that is autologous or genetically identical to the human immune system, which are discussed with examples of their usefulness in modeling human cancer immunotherapies.